Brookline Village, general view of the U.S. Postal Building, Brookline, Massachusetts 2 of 2. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a building in the Brookline Village area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Brookline Village (2) Gen. view w/US PO Bldg Walking Tour 1978.; Binder Number 4. Pocket Number: 14.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1978.; Apply to the DCA for access to the physical slides.